2006
DOI: 10.1111/j.1471-8286.2006.01595.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of new microsatellite loci in the Pacific white shrimp Litopenaeus vannamei and cross‐species amplification in other penaeid species

Abstract: The goal of the present study was to obtain valuable microsatellite markers useful in genetic approaches of the shrimp Litopenaeus vannamei, an important aquaculture species of the world. Eight loci produced suitable polymorphic patterns with allele number ranging from two to 12 and expected heterozygosity from 0.18 to 0.89. Cross‐species amplification was successfully performed in five other penaeid species (Litopenaeus schmitti, Farfantepenaeus brasiliensis, Farfantepenaeus paulensis, Xiphopenaeus kroyeri an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Four primer sets, Pvan1758 and Pvan1815 (Cruz et al, 2002) along with Lvan1 and Lvan7 (Freitas et al, 2007), were used in a 25 μL reaction volume containing 50-150 ng of DNA, 0.2 mM of each dNTP, 7.5 pmoles μL -1 of each primer, 1.5-2.5 mM MgCl 2 , 1 unit of Taq DNA Polymerase and 1 to 1.25x PCR buffer. The Master Mix (2.5X) kit (Eppendorf) was used for the Lvan1 and Lvan7 loci.…”
Section: Amplification Of Microsatellite Locimentioning
confidence: 99%
See 1 more Smart Citation
“…Four primer sets, Pvan1758 and Pvan1815 (Cruz et al, 2002) along with Lvan1 and Lvan7 (Freitas et al, 2007), were used in a 25 μL reaction volume containing 50-150 ng of DNA, 0.2 mM of each dNTP, 7.5 pmoles μL -1 of each primer, 1.5-2.5 mM MgCl 2 , 1 unit of Taq DNA Polymerase and 1 to 1.25x PCR buffer. The Master Mix (2.5X) kit (Eppendorf) was used for the Lvan1 and Lvan7 loci.…”
Section: Amplification Of Microsatellite Locimentioning
confidence: 99%
“…Microsatellite analyses have been used to assess genetic variation in several penaeid species, such as L. vannamei (Wolfus et al, 1997), Marsupenaeus japonicus (Moore et al, 1999), L. stylirostris (Bierne et al, 2000), Penaeus monodon (Tassanakajon et al, 1998;Brooker et al, 2000;Pongsomboon et al, 2000, Xu et al, 2001, Litopenaeus schmitti (Maggioni et al, 2003;Borrel et al, Genetics and Molecular Biology, 30, 4, 1156-1160(2007 Copyright by the Brazilian Society of Genetics. Printed in Brazil www.sbg.org.br 2004) and Litopenaeus setiferus (Ball and Chapman, 2003) but, however, little is known on the genetics of the Brazilian L. vannamei broodstocks Galetti Jr 2002, 2005;De Francisco and Galetti Jr, 2005;Gonçalves et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The penaeid shrimp Litopenaeus vannamei is considered one of the most important marine shrimp aquaculture species (Pérez, Ortiz, Zhinaula, Gonzabay, Calderón & Volckaert 2005). A recent review of the literature on microsatellite markers in Pacific white shrimp has reported approximately 150 polymorphic loci, mostly isolated from anonymous regions of the genome (Freitas, Jesus & Galetti 2007). Although dbEST (expressed sequence tags database) has been used to isolate microsatellites in shrimp species (Wang, Guo, Zhang, Meng, Qiu, Liu & Zhang 2009), it is poorly known in L. vannamei (Pérez et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In several regions of the world, shrimp Litopenaeus vannamei (Boone, 1931) is one of the most widely used species in the production of cultured marine shrimps (Freitas et al 2007), due to its characteristics of high adaptation, rapid growth, and high survival rates to adverse environmental conditions (Briggs et al 2004). Originally from the Eastern Pacific, this species is used by shrimp farmers throughout the Western Atlantic (Tavares 2011).…”
Section: Introductionmentioning
confidence: 99%